The Oxford handbook of international business strategy - Mellahi, Kamel,; Meyer, Klaus,; Narula, Rajneesh, 1963-; Surdu, Irina,; Verbeke, Alain, (Oxford handbooks online., 2020)
Multinational enterprises must contend with increasingly challenging conditions in the international business environment. This handbook explores how classic principles of international competitive strategy are transformed in today's markets and provides suggestions on how firms can develop effective strategies to respond to these transformations.